2019
DOI: 10.3390/nu11030598
|View full text |Cite
|
Sign up to set email alerts
|

Glycomacropeptide Bioactivity and Health: A Review Highlighting Action Mechanisms and Signaling Pathways

Abstract: Food-derived bioactive peptides are reported as beneficial and safe for human health. Glycomacropeptide (GMP) is a milk-protein-derived peptide that, in addition to its nutritional value, retains many biological properties and has therapeutic effects in several inflammatory disorders. GMP was shown under in vitro and in vivo conditions to exert a number of activities that regulate the physiology of important body systems, namely the gastrointestinal, endocrine, and immune systems. This review represents a comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
59
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(62 citation statements)
references
References 80 publications
0
59
0
3
Order By: Relevance
“…GMP is a peptide derived from milk that exhibits biological activities with positive impact on human health [ 26 ]. In the present study, we demonstrated that prophylactic GMP administration induces a significant reduction in the development of FA by diminishing the IgE and IgG1 antibody response, the allergic clinical manifestations, and the intestinal inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GMP is a peptide derived from milk that exhibits biological activities with positive impact on human health [ 26 ]. In the present study, we demonstrated that prophylactic GMP administration induces a significant reduction in the development of FA by diminishing the IgE and IgG1 antibody response, the allergic clinical manifestations, and the intestinal inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…GMP is free from phenylalanine residues, which allows it to be used as a protein-based ingredient in the formulation of food products for the nutrition of phenylketonuria patients [ 25 ]. Many different biological activities have been attributed to GMP [ 26 ]. Among them, the immune-modulatory and anti-inflammatory effects of orally administered GMP.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the different modifications CGMP is quite heterogeneous. (1,45) The reference-drink consisted of 15 g of skimmed milk powder and flavourings. Similarity of taste and texture was optimised to secure participant blinding.…”
Section: Methodsmentioning
confidence: 99%
“…Whey protein has been shown to induce satiety to a greater extent than other protein sources such as casein, soya and egg albumin [ 11 , 12 ]. There is some evidence that CGMP influences hormone responses affecting satiety [ 13 , 14 , 15 ]. However, human studies investigating the effect of CGMP on food intake and satiety have resulted in mixed findings [ 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Gut absorption of protein is thought to modulate satiety, although the influence of the protein source and individual amino acids on the control of food intake is not completely understood. It involves complex pathways that affect vagus-mediated signals, satiety related hormones and their metabolites (including the peptide ghrelin, cholecystokinin (CCK), glucagon-like peptide-1 (GLP-1), glucose dependent insulinotropic polypeptide (GIP) and peptide tyrosine–tyrosine (PYY)) [ 11 , 15 , 20 , 21 , 22 , 23 ]. Some blood amino acids, particularly leucine, lysine, tryptophan, isoleucine and threonine, are linked to satiety responses [ 24 , 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%